It Is “All About Relationships” in Lifestyle Programmes for Adults Living With Type Two Diabetes Underpinned by a Person/Whānau-Centred Care Approach - Hale, Leigh; Higgs, Christopher; Keen, Donna; Smith, Catherine (Frontiers in Rehabilitation Sciences, 2022)
Background: Lifestyle programmes are important in the management of type 2 diabetes (T2D). The Diabetes Community Exercise Programme (DCEP) is an exercise and educational programme for adults living with T2D with the aim of enhancing exercise self-efficacy and supporting wellbeing. DCEP is underpinned by a model of person-centred care and the spirit of Motivational Interviewing. Person-centred care models in the context of rehabilitation and long-term health conditions are still evolving. This paper explores what those involved in DCEP perceived important to its person-centeredness. Method: An evaluative qualitative methodological approach was used with data collected by open-ended interviews at completion of the initial 12-week (twice-a-week) part of DCEP. Interviews were audio-recorded and transcribed verbatim. Participants were 16 DCEP attendees and 13 healthcare professionals (HCPs) involved in DCEP delivering. Data were analysed using the General Inductive Approach. Results: The three interconnected themes constructed from the analysis were ‘It’s all about relationships’, Balancing the Outside World, and Empowering Knowledge. Through the experience and motivation of positive person-centred relationships, DCEP addressed attendees’ T2D health needs, but they were constantly balancing these needs with those of family, employers, finances, other health needs and life interests. DCEP relationships facilitated ongoing discussions between attendees and between attendees and HCPs. The ability to discuss in a supportive and non-judgmental environment helped attendees to make sense and process the information they gained at DCEP. This empowering knowledge in turn helped attendees to work out ways of balancing the outside world and thus better address their T2D needs. Conclusion: It is ‘all about relationships’ was key to DCEP’s person-centred approach – all other factors related back to the development and maintenance of relationships. These relationships were between all involved: the attendees, their family, the wider community, the healthcare provider organisations, and the HCPs and personnel involved in delivering DCEPs. These relationships created an accepting, understanding and social atmosphere that enabled attendance and facilitated both knowledge exchange and ability to exercise, both considered to be beneficial by attendees. Importantly, these relationships took time to develop, but the benefits were worth the investment.